A Reassessment of the Chronostratigraphy of Late Miocene C3–C4 Transitions. Issue 7 (10th July 2020) - Tauxe, L.; Feakins, S. J.
Abstract: Combining magnetostratigraphic and carbon isotopic data for the late Miocene can provide a temporal framework for an isotopic shift first documented in soil carbonate nodules of northern Pakistan. The shift has been interpreted as a change in vegetation from trees and shrubs (using the C3 photosynthetic pathway) to grassland (using the C4 pathway). The cause of the event has been hotly debated and its timing is close to a shift in carbon isotopes in the marine realm. Further understanding depends critically on chronology. Unfortunately, temporal calibration of the various records published over decades relied on different time scales. To address the lack of a consistent chronology, we have reevaluated the constraints for the carbon isotopic shifts recorded from the Indian subcontinent. These show a diachronous transition ranging in age from about 7.8 Ma in Pakistan to as late at 6 Ma in Nepal. The record from IODP Expedition 355 Site U1457, drilled on the Indus fan shows that the transition in peninsular India began at about 7.2 Ma. Similar records from the African margin saw an earlier shift to C4 dominance starting around 10 Ma and those from Australia and South America transitioned later, during the Pliocene. The diachroneity around the globe does not invalidate pCO2 as a driver, but is consistent with it being one of several drivers of the global C4 expansion. Plain Language Summary: Grasslands expanded on the Indian subcontinent in the late Miocene. Precise chronological control is critical to compare the timing of the expansion between regions and to evaluate the possible causes (and consequences) of the ecological transformation. Here we take a new look at published records from Pakistan, India, and Nepal and update the age models to a modern geomagnetic reversal time scale. We then compare these to new records from the marine sediments obtained during IODP Expedition 355 to the Indus Fan and others from the African margin. Based on microfossil appearance and paleomagnetic constraints, the timing of the transition to C4 vegetation is found to be asynchronous across the globe, probably initiating in Africa after 10 Ma, then proceeding to Pakistan at around 7.8 Ma and reaching Nepal by ∼⃒6 Ma. Elsewhere in the world (Australia and Argentina) the transition happened several million years later. We also review recent model and proxy evidence to find the causes of the C4 grassland expansion. Key Points: A change from forest to grassland ecologies began in the late Miocene but chronologies of the published records are based on different time scales Recalibration to a consistent time scale demonstrates the diachroneity of the ecological change in different places around the globe New constraints link a major C4 expansion in the late Miocene with evidence for carbon cycle perturbations